Prevalence of different bacterial species in the uterine fluid of repeat breeder cows (Journal of Bangladesh Academy of Sciences, 2023)
Among the diverse factors, bacterial infections in the reproductive tract potentially cause of repeat breeding in dairy cows. The present research was conducted to appraise the uterine organism in healthy fertile cows (HFC) and repeat breeder cows (RBC) and to establish a relationship with previous disease or disease conditions. A total of 43 uterine samples were collected from 10 healthy fertile and 33 RB cows for bacteriological study. Among RBC, 39.4% harbored bacterial isolates of E. coli (30.3%), Staphylococcus aureus (27.3%), Staphylococcus epidermidis (15.2%), and Bacillus spp. (18.2%). Total Viable Count (TVC) of RBC with isolates was higher (1.81 x 1010CFU/mL) than in normal fertile cows (1.3x1010 CFU/mL). No bacterial isolates were recovered from 60.6% RBCs and 80.0% healthy fertile cows. A single, mixed infection of two, three and four bacterial species was observed in the uterine discharge of 12.1%, 9.1%, 12.1% and 6.1% RBC, respectively. From animal demographic data of RBC, the sub-clinical mastitis, acute mastitis, endometritis, dystocia, retention of placenta, and abortion were 42.4%, 39.4%, 39.4%, 12.1%, 9.1%, and 6.1%, respectively. In contrast, the presence of dystocia, endometritis, subclinical mastitis, retention of placenta and abortion was recorded in 50%, 30%, 30.8%, 23.1%, and 15.4% of healthy cows, respectively. This result could help the veterinarian to design the proper antibacterial therapy based on bacteria isolates in RBCs.J. Bangladesh Acad. Sci. 47(1); 33-42: June 2023